Analisa Peran Keluarga Dalam Pelibatan Budaya Anti Kekerasan Seksual pada Anak - Syahril Ramadhon Alamsyah; Boris Brahmono; Novi Yatri Pratiwi (Comit: Communication, Information and Technology Journal, 2023)
This article provides a comprehensive overview of the role of the family in engaging in a culture of anti-sexual violence against children. This study examines sexual violence against children, the prevalence and risk factors for various types of sexual violence and discusses the knowledge and perceptions of the community regarding these acts of violence. Also examines the role of the family in a culture of anti-sexual violence in children and critically examines the meaning of a culture of anti-sexual violence in children, a variety of literature studies is the main qualitative method in this article accompanied by the main focus of studies on the role of the family in anti-violence in children. examines specific cultural factors that do not only focus on cultural factors in general, but must examine the culture of non-violence in the context of modern society and the consensus of international standards on human rights which become recommendations for further research. Keywords: Family Role, Culture, sexual violence against children